2011
DOI: 10.1186/1476-511x-10-179
|View full text |Cite
|
Sign up to set email alerts
|

Different sources of omega-3 polyunsaturated fatty acids affects apparent digestibility, tissue deposition, and tissue oxidative stability in growing female rats

Abstract: BackgroundNumerous health benefits associated with increased omega-3 polyunsaturated fatty acid (n-3 PUFA) consumption has lead to an increasing variety of available n-3 PUFA sources. However, sources differ in the type, amount, and structural form of the n-3 PUFAs. Therefore, the objective of this study was to determine the effect of different sources of ω-3 PUFAs on digestibility, tissue deposition, eicosanoid metabolism, and oxidative stability.MethodsFemale Sprague-Dawley rats (age 28 d) were randomly assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
57
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 56 publications
12
57
2
1
Order By: Relevance
“…An increase in the liver levels of DHA, which has a structural role (whereas EPA is preferentially utilized for fatty acid oxidation or eicosanoid synthesis) [33] was also observed by Tou et al [34]. We can however exclude that these modifications were in some way responsible for the observed reduced transport activity of the mitochondrial CIC (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…An increase in the liver levels of DHA, which has a structural role (whereas EPA is preferentially utilized for fatty acid oxidation or eicosanoid synthesis) [33] was also observed by Tou et al [34]. We can however exclude that these modifications were in some way responsible for the observed reduced transport activity of the mitochondrial CIC (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…Hamazaki et al [25], Animal Study 1, compared TAG, PL, EE; Yang et al [26], Animal Study 2 -compared TAG, EE and methyl esters; Ikeda et al [27], Animal Study 3 -compared TAG, FFA and EE; Batetta et al [28], Animal Study 4 -compared fish oil and krill oil; Di Marzo et al [29], Animal Study 5 -compared fish oil and krill oil; Tou et al [30], Animal Study 6 -compared fish oil and krill oil;…”
Section: Literature Search; Methods and Results Of Selected Studiesmentioning
confidence: 98%
“…Of these, three studies [28][29][30] compared the bioavailability of fish oil and krill oil in which Batetta et al [28] and Di Marzo et al [29] focused on the comparison of the production of endocannabinoids from fish oil and krill oil in Zucker rats.…”
Section: Methods Of Animal Studiesmentioning
confidence: 98%
“…Indeed, in vivo studies have reported higher bioavailability of omega-3 fatty acids when delivered as krill oil rather than as fish oil, which was partly attributed to the fact that the polyunsaturated fatty acids were part of phospholipids in krill oil(Kohler, Sarkkinen, Tapola, Niskanen, & Bruheim, 2015;Schuchardt et al, 2011). Conversely, other in vivo studies have reported a higher bioavailability of polyunsaturated fats from fish oils than from krill oil(Tou, Altman, Gigliotti, Benedito, & Cordonier, 2011). Further research is required to better understand the behavior of krill oil within the GIT, and how this may be used to control lipid digestion and bioactive release.After passing through the small intestinal stage, all the emulsions contained relatively large particles as detected by both light scattering and confocal microscopy .…”
mentioning
confidence: 91%